![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
求问这题怎么做!!第八题
1个回答
展开全部
令f(x)=x^(a^x),g(x)=x^x,h(x)=x^(x^a)
1、清举启lnf(x)=(a^x)lnx
f'答基(x)/f(x)=lna*(a^x)*lnx+(a^x)/x=(a^x)*(lna*lnx+1/x)
f'(x)=x^(a^x)*(a^x)*(lna*lnx+1/x)
2、答如lng(x)=xlnx
g'(x)/g(x)=lnx+1
g'(x)=(x^x)*(lnx+1)
[a^(x^x)]'=lna*a^(x^x)*(x^x)'=lna*a^(x^x)*(x^x)*(lnx+1)
3、lnh(x)=(x^a)lnx
h'(x)/h(x)=alnx*[x^(a-1)]+x^(a-1)=[x^(a-1)]*(alnx+1)
h'(x)=x^(x^a+a-1)*(alnx+1)
所以dy/dx=x^(a^x)*(a^x)*(lna*lnx+1/x)+lna*a^(x^x)*(x^x)*(lnx+1)+x^(x^a+a-1)*(alnx+1)
1、清举启lnf(x)=(a^x)lnx
f'答基(x)/f(x)=lna*(a^x)*lnx+(a^x)/x=(a^x)*(lna*lnx+1/x)
f'(x)=x^(a^x)*(a^x)*(lna*lnx+1/x)
2、答如lng(x)=xlnx
g'(x)/g(x)=lnx+1
g'(x)=(x^x)*(lnx+1)
[a^(x^x)]'=lna*a^(x^x)*(x^x)'=lna*a^(x^x)*(x^x)*(lnx+1)
3、lnh(x)=(x^a)lnx
h'(x)/h(x)=alnx*[x^(a-1)]+x^(a-1)=[x^(a-1)]*(alnx+1)
h'(x)=x^(x^a+a-1)*(alnx+1)
所以dy/dx=x^(a^x)*(a^x)*(lna*lnx+1/x)+lna*a^(x^x)*(x^x)*(lnx+1)+x^(x^a+a-1)*(alnx+1)
追问
[a^(x^x)]'=lna*a^(x^x)*(x^x)'=lna*a^(x^x)*(x^x)*(lnx+1)
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询